Black Race and Body Mass Index Are Risk Factors for Rhabdomyolysis and Acute Kidney Injury in Trauma. Issue 3 (15th March 2020) - Grigorian, Areg; Gabriel, Viktor; Nguyen, Ninh T.; Smith, Brian R.; Schubl, Sebastian; Borazjani, Boris; Joe, Victor; Nahmias, Jeffry
Abstract: Purpose: Obesity has been shown in a single-center study to be a risk factor for rhabdomyolysis. More recently, sickle cell trait, known to be more prevalent in blacks, has been shown to be a risk factor for rhabdomyolysis. We hypothesized that in trauma patients, black race and a higher body mass index (BMI) are associated with risk for rhabdomyolysis and acute kidney injury (AKI). Materials and Methods: The National Trauma Data Bank (NTDB) was queried (2013–2015) to identify patients age ≥18 years and grouped by BMI: normal (18.5–24.99 kg/m 2 ), underweight (16.5–18.49 kg/m 2 ), overweight (25–29.99 kg/m 2 ), obese (30–34.99 kg/m 2 ), severely obese (35–39.99 kg/m 2 ), and morbidly obese (≥40 kg/m 2 ). A multivariable logistic regression model was used to assess whether a higher BMI or black race was associated with rhabdomyolysis or AKI. Results: After adjusting for covariates, severe obesity (odds ratio (OR) = 1.42, confidence interval (CI) = 1.01–1.99, p < .001), morbid obesity (OR = 1.46, CI = 1.04–2.06, p < .001), and black race (OR = 1.52, CI = 1.24–1.88, p < .001) were associated with higher risk for rhabdomyolysis. Patients that were overweight (OR = 1.17, CI = 1.11–1.24, p < .001), obese (OR = 1.32, CI = 1.24–1.41, p < .001), severely obese (OR = 1.72, CI = 1.59–1.86, p < .001), morbidly obese (OR = 1.77, CI = 1.64–1.92, p < .001), or black (OR = 1.31, CI = 1.24–1.38, p < .001) were associated with higher risk for AKI. Conclusions: Black race was associated with an increased risk of rhabdomyolysis as well as AKI in trauma. BMI ≥25 kg/m 2 was associated with increased risk for AKI with the morbidly obese having the highest risk. BMI ≥35 kg/m 2 was found to be associated with increased risk of rhabdomyolysis. Future studies should investigate the role for routine screening of these high-risk populations and other potential associated factors such as adherence to weight-based fluid resuscitation.